Evaluation of the Psychometric Properties of NOC Outcomes "Anxiety Level" and "Anxiety Self‐Control" in a Portuguese Outpatient Sample. Issue 3 (25th January 2017) - Sampaio, Francisco Miguel Correia; Araújo, Odete Sofia Silva Lomba; Sequeira, Carlos Alberto da Cruz; Lluch Canut, María Teresa; Martins, Teresa
Abstract : PURPOSE: To adopt the language and to evaluate the psychometric properties of "Anxiety level" and "Anxiety self‐control" NOC outcomes in Portuguese adult patients. METHODS: Methodological design. FINDINGS: The final European Portuguese version of the NOC outcome "Anxiety level, " composed by 16 indicators, proved excellent internal consistency. Exploratory factor analysis (EFA) was forced to three factors. The NOC outcome "Anxiety self‐control, " composed of nine indicators, demonstrated a questionable internal consistency. EFA was forced to two factors. CONCLUSIONS: European Portuguese versions of the studied NOC outcomes proved to be tools with acceptable psychometric properties for evaluating anxiety in Portuguese patients. IMPLICATIONS FOR NURSING PRACTICE: This study contributed to the development of NOC language and to the enrichment of nursing's body of knowledge. OBJETIVO: Adaptar a linguagem e avaliar as propriedades psicométricas dos resultados NOC "Nível de ansiedade" e "Autocontrolo da ansiedade" em utentes portugueses adultos. MÉTODOS: Estudo metodológico. RESULTADOS: A versão portuguesa do resultado NOC "Nível de ansiedade", composta por 16 indicadores, apresentou uma excelente consistência interna. A análise fatorial exploratória (AFE) foi forçada a três dimensões. O resultado NOC "Autocontrolo da ansiedade", composto por nove indicadores, apresentou uma consistência interna questionável. A AFE foi forçada a duas dimensões. CONCLUSÕES: As versões portuguesas dos resultados NOC estudados são instrumentos com propriedades psicométricas aceitáveis para avaliar a ansiedade em utentes portugueses. IMPLICAÇÕES PARA A PRÁTICA DE ENFERMAGEM: Este estudo contribuiu para o desenvolvimento da linguagem NOC e para enriquecer o corpo de conhecimento de Enfermagem.